The Strategy of Madrasah Development Amidst Globalization Challenges - Firmansyah, Firmansyah; Muhammad Zuhdi; Karoma (Universitas Islam Indonesia, 2023)
As an educational institution born from the cradle of Islamic civilization, madrasahs have played a role in the advancement of the Muslim community in the past. However, in the midst of this era of globalization, madrasahs face complex challenges. This research aims to describe the development of madrasahs in the dynamics of Islamic education and the strategic steps madrasahs take in facing the era of globalization. This study is a literature review that uses documentation as the method of data collection, while the analysis technique employs inductive analysis. The results of this research indicate that in this era of globalization, madrasahs encounter two main challenges: 1) internal challenges, such as the low quality and competitiveness of madrasah graduates; and 2) external challenges, namely Islamophobia in the global community, especially in the West. To address internal issues, integrated improvements involving all elements of madrasah management need to be pursued. External issues need to be approached with a new marketing model that utilizes contemporary communication patterns to combat negative stigma against madrasahs and simultaneously create a positive trend towards the image of Islamic educational institutions and Islam itself.